Dissociative amnesia: a case report (Bangladesh Journal of Psychiatry, 2021)
Functional retrograde amnesia or dissociative amnesia is often associated with physical and/or psychological trauma. We encountered a female patient ageing 18 years who could not recall the last 5 months of her life after stressful life event. This case report describes a patient suffering from retrograde episodic-autobiographical amnesia for around 1 month after a discord with her husband. She forgot that she was married and forgot every incident which was related to the marriage. Her semantic memories and social abilities were largely preserved though she couldn’t recall people she met within last five months. All the examinations were negative for organic pathology. Same stress can result in variable presentation in different persons. This case report focused on stress induced dissociative amnesia and recovery in 18 years old women.Bang J Psychiatry 2021;35(1): 17-18